ISU-ISU BERBANGKIT DARI HAK HADANAH DAN HAK PERWALIAN ANAK: The Issues Arising from The Custody and Guardianship Rights of Children - Noor, Zanariah (Jurnal Syariah, 2019)
The rights of custody and guardianship of the children are different from each other. Custody is primarily vested in the female, especially the mother, and guardianship is the right of the male, such as the father and grandfather. Both rights require different obligations from the mother and father. This article discusses the issues arising from custody and guardianship rights during marriage as well as after divorce. The issues that will be discussed are breach of duties by the custodian or guardian regarding child maintenance and access. The discussion also covers the issue of the choice of religion of the child, child habitual residence as well as the issue of travelling overseas with the child.